Characterization of the Gramillin Virulence Factor from Fusarium graminearum in Barley (Hordeum vulgare L.) - Power, Monique (Université d'Ottawa / University of Ottawa, 2023)
Fusarium head blight is a devastating fungal disease of cereals caused by the pathogen Fusarium graminearum that leads to important economic losses due to diminished yields and grain downgrading. F. graminearum deploys several secondary metabolites known as virulence factors to facilitate its invasion of host tissues. These include the gramillins, a group of bicyclic lipopeptide ionophores that cause cell death and increased virulence in Arabidopsis, maize, and barley, but not wheat. Ionophores are involved in many plant-microbe interactions, but current knowledge of the molecular mechanisms governing host response to these molecules is limited. Susceptibility to gramillin varies among cultivars of affected species, but the basis for insensitivity has not yet been described, nor has the function of gramillin during infection. Here, we establish ion leakage as a method to survey Canadian barley for sensitivity, demonstrate that insensitivity to gramillin is likely mediated by a plant protease rather than inducible immune responses, and suggest a possible function of gramillin in positively regulating the expression of other fungal virulence factors during infection. This contributes to deepening our understanding of cyclic lipopeptide ionophores and their role during plant-microbe interactions.
Keywords: Gramillin; Fusarium graminearum; Virulence factor; Cyclic lipopeptide; Ionophore